Create to communicate : art activities for the English as a foreign language classroom (Office of English Language Programs : Bureau of Educational and Cultural Affairs : United States Department of State, 2013)
This book is intended for English language teachers who would like to reap the benefits that the visual arts provide, but are unsure of where or how to begin. By providing language objectives matched with art ideas and guidelines, this book seeks to use the arts as a tool to build and strengthen English reading, writing, listening, and speaking skills and develop the confidence students need to take risks and explore within a new language. Designed to supplement regular coursework, the purpose of this book is not to provide art lessons, but rather to provide ideas of how to incorporate the arts into the language classroom to make English accessible and understandable to students. This book is ideal for Access English Microscholarship Teachers, primary and secondary school EFL teachers worldwide, American Spaces, English language tutors, and English Teaching Assistants (Fulbright).